Borderline malignant change in recurrent müllerian papilloma of the vagina. Issue 11 (November 1998) - Dobbs, S P; Shaw, P A; Brown, L J; Ireland, D
Abstract : Malignant change occurred in a benign, recurrent vaginal müllerian polyp. The patient, a 49 year old woman with cerebral palsy, presented with a polypoid mass in the vagina. At four years of age she had presented with a haemorrhagic polyp, and over the following years she had recurrent irregular bleeding and regrowth of the polypoidal mass, requiring a total of 10 operations to excise the polyp. Histological examination of the specimen showed typical müllerian features with tubal, endometrioid, and endocervical cell types. There were significantly abnormal nuclei, indicating low grade or borderline malignancy. Review of previous biopsies showed similar müllerian features but no atypia. This is the first reported case of borderline malignant change in a previously benign recurrent müllerian papilloma of the vagina. Definitive radical surgery or radiotherapy is contraindicated in this patient and she remains under follow up.